Insights into the microbial L-asparaginases: From production to practical applications - Sharma D.; Singh K.; Singh K.; Mishra A. (My University, 2025)
L-asparaginase is a valuable protein therapeutic drug utilized for the treatment of leukemia and lymphomas. Administration of asparaginase leads to asparagine starvation causing inhibition of protein synthesis, growth, and proliferation of tumor cells. Besides its clinical significance, the enzyme also finds application in the food sector for mitigation of a cancer-causing agent acrylamide. The numerous applications ensue huge market demands and create a continued interest in the production of costeffective, more specific, less immunogenic and stable formulations which can cater both the clinical and food processing requirements. The current review article approaches the process parameters of submerged and solid-state fermentation strategies for the microbial production of the L-asparaginase from diverse sources, genetic engineering approaches used for the production of L-asparaginase enzyme and major applications in clinical and food sectors. The review also addresses the immunological issues associated with the L-asparaginase usage and the immobilization strategies, drug delivery systems employed to circumvent the toxicity complications are also discussed. The future prospects for microbial Lasparaginase production are discussed at the end of the review article. © 2019 Bentham Science Publishers.